2015
DOI: 10.1186/s13028-015-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and epidemiological patterns of perinatal lamb mortality in Norway

Abstract: BackgroundPerinatal mortality is a major cause of loss in the sheep industry. Our aim was to explore time trends in crude population stillbirth and neonatal mortality rates in Norway. We used data on 6,435,715 lambs from flocks enrolled in the Norwegian Sheep Recording System (NSRS) from 2000 through 2010 for descriptive analysis of trends. Longitudinal patterns of mortality rates were compared for lambs within different levels of variables suspected to be associated with perinatal loss.ResultsThere was an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Methodological approaches have variously relied on veterinary student-administered 22 or farmeradministered questionnaires, 23 farmer-performed neonatal lamb postmortem examinations 24 or a combination of veterinary or lock-manager diagnostic postmortem procedures 25 to determine mortality or cause-speciic mortality rates. Terminology such as 'neonatal' or 'perinatal' also vary between studies [24][25][26][27][28] as have rate measures such as 'mortality between scanning and sale' 29 and 'mortality between 24 hours and weaning'. 25 Identiication of a suitable rate measure in such studies is challenging as the denominator is constantly changing during the lambing season.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological approaches have variously relied on veterinary student-administered 22 or farmeradministered questionnaires, 23 farmer-performed neonatal lamb postmortem examinations 24 or a combination of veterinary or lock-manager diagnostic postmortem procedures 25 to determine mortality or cause-speciic mortality rates. Terminology such as 'neonatal' or 'perinatal' also vary between studies [24][25][26][27][28] as have rate measures such as 'mortality between scanning and sale' 29 and 'mortality between 24 hours and weaning'. 25 Identiication of a suitable rate measure in such studies is challenging as the denominator is constantly changing during the lambing season.…”
Section: Discussionmentioning
confidence: 99%
“…For both sheep and goats, the variation in the time periods covered by different studies was too great to allow direct comparisons. In sheep, two papers noted that stillbirth and perinatal mortality rates were higher than at any age (Holmoy & Waage, 2015); Voigt et al, 2019), while other authors report the largest proportion of mortalities occurred within 24 hours of birth (Binns et al, 2002), or within first week (Gokce & Erdogan, 2009;Gokce et al, 2013;Khan et al, 2006). Holmoy et al (2017) reported that 80% of neonatal lamb mortalities occurred within the first two days of life.…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
“…Lamb survival rates to weaning across 29 studies clearly indicate triplet lambs (mean value across studies 67.5%) have lower survival than their singleton (89.5%) and twin (85.5%) counterparts (Table 2). Most lambs die within three days of birth but, triplets can have higher loss rates past this period (Kleeman et al 1993;Hinch and Brien 2014;Holmøy et al 2014Holmøy et al , 2017Holmøy and Waage 2015;Refshauge et al 2016), presumably driven by a mismatch in milk supply and demand (see later section). Ferreira et al (2015) reported that when artificially reared, after one day of age, triplet survival did not differ from singletons and twins.…”
Section: Survivalmentioning
confidence: 99%